Implementasi Pendidikan Moderasi Beragama Pondok Di Pesantren Kabupaten Sorong - Muhammad Satir; Muhammad Rusdi Rasyid; Arini Rahmadana (LPPM IAIN Sorong, 2022)
The purpose of this study is to describe the phenomenon of implementation and implementation model of religious moderation education in Islamic boarding schools in Sorong Regency which has a pluralist, multiethnic and multicultural population. This is a descriptive-qualitative research with three Islamic boarding schools as research locations. Data were obtained from Kiayi, educators and students, using observation techniques, in-depth interviews, FGDs and documentation. The results of the study indicate that the process of implementing religious moderation education in the three Islamic boarding schools implemented automatically by the lessons of the students at the Islamic Boarding School. The implementation of religious moderation is reflected in several aspects, namely; national commitment through activities that contain the spirit of nationalism and respect for differences, understanding of tolerance and anti-radicalism obtained through the understanding of teachers and teaching materials; accommodative behavior towards local culture is reflected in the implementation of barzanji, yasinan, and tahlil. The implementation of moderation education is also accommodated through the integration of general formal education with Islamic boarding school diniyah education, then the teacher perspective through religious moderation and the most by the kitab kuning which contains a message of moderation through lessons on Aqidah, Sharia and Morals, especially in the kitab Aqidatul Awam, Akhlakul lil banin, Khulasoh and Risalah. Moderation model pattern in Islamic boarding schools in Sorong shows pattern, (1) The integration model of learning with Islamic material content that contains moderation values, especially through the teaching of The kitab kuning. The next pattern is (2) The collaboration model of Islamic boarding school curriculum with formal madrasas, dan the collaboration model of Islamic boarding school curriculum with local culture, and globalization. Keywords: Islamic Boarding School, Religious Moderation, The Kitab Kuning, Salafiyah-Modern